Pituitary Research Through Rat Models: Liu Shih-Hao's Studying in London and Far-Reaching Influence - CHEN Zhenghua; LI Naishi (Xiehe Yixue Zazhi)
Liu Shih-Hao, the founder of endocrinology in China, conducted research on the hypothalamic-pituitary-gonadal axis using rats as experimental subjects during his academic training in the United Kingdom in the late 1930s. This aspect of his work has not yet received due attention in prior scholarship. Accordingly, this article provides an overview of this series of studies and situates these relatively micro-level events in medical history within the broader context of Liu Shih-Hao's personal academic trajectory and the historical development of endocrinology at the time. Furthermore, by connecting these early investigations with Liu's later report, The Direction of Endocrinology Research Development, delivered more than two decades afterward, this paper explores the underlying linkages between them. Through this analysis, the study aims to elucidate the rich historiographical significance of these investigations, thereby contributing to a more comprehensive understanding of Liu Shih-Hao's academic legacy as well as the establishment and evolution of endocrinology in China.